1996
DOI: 10.1007/bf00123916
|View full text |Cite
|
Sign up to set email alerts
|

Automated knowledge acquisition for the surface-mount PWB assembly domain

Abstract: The development of knowledge-based (or expert) systems for the surface-mount printed wiring board (PWB) assembly domain requires the understanding and regulation of several complex tasks. While the knowledge base in an expert system serves as a storehouse of knowledge primitives, its design and development is a bottleneck in the expert system development lifecycle. Therefore the development of an automated knowledge acquisition (KA) facility (or KA tool) would facilitate the implementation of expert systems fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…manufacturability, test) [7,[17][18][19][20][21]. Srihari's research group have actively researched the development of advisory systems for surface mount technology (SMT) assembly since the early 1990s [7,[22][23][24]. These systems are mainly limited in scope to solderability, reflow and cleanability issues.…”
Section: Research Contextmentioning
confidence: 99%
“…manufacturability, test) [7,[17][18][19][20][21]. Srihari's research group have actively researched the development of advisory systems for surface mount technology (SMT) assembly since the early 1990s [7,[22][23][24]. These systems are mainly limited in scope to solderability, reflow and cleanability issues.…”
Section: Research Contextmentioning
confidence: 99%
“…In the mid 1990s, some electronics manufacturing knowledge bases have been developed for various PCBA lines and applications [6][7][8][9][10][11]. None of these studies reported an integrated PCBA process planning environment.…”
Section: Generic Overviewmentioning
confidence: 99%
“…Wu and Srihari (1995) present a conceptual model of an automated knowledge acquisition tool that uses a goal-driven mechanism to elicit knowledge on a level-by-level basis. The tool is also constructed with a feature of domain independence.…”
Section: The Introduction To the Researchmentioning
confidence: 99%